Functional Analysis of the Staphylococcus aureus Collagen Adhesin B Domain - Snodgrass, James L. (American Society for Microbiology, 1999)
The Staphylococcus aureus collagen adhesin (CNA) occurs in at least four forms that differ in the number (one, two, three, or four) of B domains. The B domains contain 187 amino acids and are located between the domains that anchor CNA to the cell envelope and the ligand-binding A domain. To determine whether a B domain is required for functional expression of CNA, we cloned the 2B cna gene from S. aureus strain Phillips and then eliminated both B domains by overlapping PCR. The absence of a B domain did not affect processing of the collagen adhesin to the cell surface or the ability to bind collagen. Based on our recent demonstration that the capsule can mask CNA on the surface of S. aureus cells (A. F. Gillaspy et al., Infect. Immun. 66:3170–3178, 1998), we also investigated the possibility that multiple B domains can extend the ligand-binding A domain outward from the cell surface and thereby overcome the inhibitory effect of the capsule. Specifically, we cloned the naturally occurring 4B CNA variant from S. aureus UAMS-639 and, by successive elimination of B domains, generated 1, 2, and 3B variants that are isogenic with respect to the 4B clone. After introducing each variant into microencapsulated and heavily encapsulated strains of S. aureus and growing cells under conditions known to affect capsule production (e.g., growth on Columbia agar), we correlated capsule production with exposure of CNA on the cell surface and the ability to bind collagen. Under no circumstance was the masking effect of the capsule reduced by the presence of multiple B domains. These results indicate that the B domains do not extend the ligand-binding A domain outward in a fashion that can overcome the inhibition of collagen binding associated with capsule production.